Pemanfaatan Aset Debitur Pasca Kepailitan: Menuju Peningkatan Nilai Ekonomi dan Manfaat Bagi Kreditur - Siregar, Mohammad Rizky (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research employs a qualitative approach with a descriptive analytical design to analyze the mechanism of debtor's asset utilization post-bankruptcy in Indonesian bankruptcy law. The primary objective of this study is to identify strategies that can enhance the economic value and benefits for creditors, as well as address the challenges and obstacles in utilizing debtor's assets post-bankruptcy. Data is collected through direct observation of asset management by curators and auction implementation, as well as secondary data analysis such as legal documents, related literature, bankruptcy court reports, and statistical data. The research findings are expected to contribute significantly to understanding and addressing the challenges in utilizing debtor's assets post-bankruptcy in Indonesia, and provide practical recommendations for creditors and other stakeholders to improve the effectiveness and efficiency of debtor's asset utilization.